Desenvolvimento de um veículo aéreo não tripulado para aplicação em agricultura de precisão - Medeiros, Fabrício Ardais (2007)
This work presents the development of the unmanned aerial vehicles (UAV) as an important option for the monitoring and remote sensing of agricultural activities. The UAV application in recognition missions has been favored and helped mainly by the its current technological state of development, like reduced cost of manufacturing, reduction in the size and weight of navigation equipments, and the need of optimizing in the corps production. For a better understanding of this project, the contents were divided into three main subjects, methodology applied for each state, performance of the prototype, monitoring and processing of acquired aerial images. The development of the UAV was focused into the methodological activities used in the project and as well as in the results generated by its application to assemble the final prototype. The material and the technique used for the production of each component of the final UAV prototype, is described through modes and phases. Under the project conditions the set prototype and the equipments used with it showed acceptable results. The acquired and processed images by the set UAV and equipments were good enough for a preliminary analysis of crops and can give support in the identification of blotch and weed invasions in specific areas of them.